RIFM fragrance ingredient safety assessment, 2-isobutyl-4-methyltetrahydro-2H-pyran-4-ol, CAS registry number 63500-71-0. (August 2019) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Francis, M.; Fryer, A.D.; et al.
Abstract: 2-Isobutyl-4-methyltetrahydro-2H-pyran-4-ol) was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data show that 2-isobutyl-4-methyltetrahydro-2H-pyran-4-ol is not genotoxic, does not have skin sensitization potential, and provided an MOE >100 for the repeated dose, developmental, and reproductive toxicity endpoints. The local respiratory toxicity endpoint was completed using the TTC (Threshold of Toxicological Concern) for a Cramer Class III material (0.47 mg/day). The phototoxicity/photoallergenicity endpoint was completed based on UV spectra and data on 2-isobutyl-4-methyltetrahydro-2H-pyran-4-ol. The environmental endpoints were evaluated; 2-isobutyl-4-methyltetrahydro-2H-pyran-4-ol was found not to be PBT as per the IFRA Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., PEC/PNEC), are <1. Highlights: 2-Isobutyl-4-methyltetrahydro-2H-pyran-4-ol, safety assessment based on RIFM's criteria. Safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.